Evaluating decontamination protocols for the isolation of Mycobacterium ulcerans from swabs. Issue 1 (December 2017) - Owusu, Enid; Newman, Mercy; Akumwena, Amos; Bannerman, Elizabeth; Pluschke, Gerd
Abstract Background Mycobacterium ulcerans (M. ulcerans ) is the causative agent of Buruli Ulcer (BU) disease. In order to inhibit the growth of the microbial contaminants during culture ofM. ulcerans, it is necessary to decontaminate BU samples with effective chemical agents. This study aimed at investigating some selected chemicals as potential decontamination agents for the isolation ofM. ulcerans from swabs. Results Povidone iodine at 0.5 and 1% exhibited the lowest contamination and recovery rate for microbial contaminants andM. ulcerans. The most effective decontamination method was the protocol using 2% cetylpyridinium chloride/4% sodium chloride (recovery rate = 53%, contamination rate = 14%). The observed difference between the recovery rate of 2% CPC/4% NaC and the other protocols was however not statistically significant (p  = 0.76). Conclusions Two percent (2%) cetylpyridinium chloride/4% sodium chloride can be conveniently used as an alternative decontamination method for the isolation ofM. ulcerans from swabs.